Biomechanical Technique Changes in Males and Females during a Prolonged Asymmetrical Lifting Task. (September 2013) - Rae, Michelle; Smith, Dave A.; Fischer, Steven L.; Croll, Jim; Albert, Wayne J.
The purpose of this study was to examine biomechanical differences between genders during a prolonged fatiguing asymmetric lifting task. Thirty-seven participants performed an asymmetrical lifting task over a period of 75 minutes at a rate of six lifts per minute. The lift envelope started from the floor directly in front of the participant to a shelf 60 degrees to the right of the sagittal plane at a normalized height to the participant's anterior superior iliac spine (ASIS). A handled box weighing 10% of the participants' predetermined maximum lifting capacity was used as the lifting object. Electromagnetic tracking sensors were used to provide kinetic and kinematic data. Eleven sensors were affixed bilaterally to the participant's hands, arms, and trunk. Strong indicators for fatigue were found after the lifting task. Ratings of Perceived Exertion (RPE) increased over time and maximal voluntary exertion in back and shoulder extension decreased post lifting. Kinematic changes were altered over time, more markedly in females than males, suggesting that biomechanical differences exist during similar tasks due to factors associated with gender. Males and females differ in their response to a fatigued state during the same asymmetric lifting task. Given that current ergonomic practice is based on gender neutralized or androcentric design, the difference in response between males and females to the same stimuli suggests that current workplace interventions may not be equally effective for both sexes.